Basal stability analysis of braced excavations with embedded walls in undrained clay using the upper bound theorem. (September 2018) - Huang, Maosong; Tang, Zhen; Yuan, Juyun
Abstract: The embedded wall has beneficial effects on the basal stability of braced excavation in clay. Conventional basal stability analysis methods cannot evaluate the lateral resistance afforded by the wall reasonably. This paper presents a new failure mechanism to evaluate the basal stability of excavations with embedded walls in undrained clay based the upper bound theorem. The proposed mechanism consists of a rigid block and three shear zones, and the horizontal reinforcing effects of wall penetration blow the excavation base are considered. The embedded wall is regarded as an elastic beam and deforms consistently with the velocities of adjacent soil in the shear zone. The elastic strain energy stored in the wall is incorporated in the upper bound calculation to increase the stability of excavation. The proposed mechanism has also been extended to the basal stability of excavations in anisotropic and non-homogeneous clay. The applicability of the proposed mechanism was validated by comparison with the results of numerical limit analysis and FEM, as well as five field cases near or at failure. Two failure field cases in anisotropic clay were also studied using the proposed mechanism. The results showed that the proposed method is capable to yield reasonable estimation by using both isotropic and anisotropic shear strength.